Direct printing of patterned three-dimensional ultrafine fibrous scaffolds by stable jet electrospinning for cellular ingrowth. (4th November 2015) - Yuan, Huihua; Zhou, Qihui; Li, Biyun; Bao, Min; Lou, Xiangxin; Zhang, Yanzhong
Abstract: Electrospinning has been widely used to produce ultrafine fibers in microscale and nanoscale; however, traditional electrospinning processes are currently beset by troublesome limitations in fabrication of 3D periodic porous structures because of the chaotic nature of the electrospinning jet. Here we report a novel strategy to print 3D poly(L-lactic acid) (PLLA) ultrafine fibrous scaffolds with the fiber diameter of approximately 2 μ m by combining a stable jet electrospinning method and an X-Y stage technique. Our approach allows linearly deposited electrospun ultrafine fibers to assemble into 3D structures with tunable pore sizes and desired patterns. Process conditions (e.g., plotting speed, feeding rate, and collecting distance) were investigated in order to achieve stable jet printing of ultrafine PLLA fibers. The proposed 3D scaffold was successfully used for cell penetration and growth, demonstrating great potential for tissue engineering applications.